Challenges in Parkinson's Disease 2016
DOI: 10.5772/62881
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Parkinson’s Disease: The Role of Copy Number Variations

Abstract: Parkinson's disease (PD), the second most common progressive neurodegenerative disorder, was long believed to be a non-genetic sporadic origin syndrome. The identification of distinct genetic loci responsible for rare Mendelian forms of PD has represented a revolutionary breakthrough, allowing to discover novel mechanisms underlying this debilitating still incurable condition. Along with single-nucleotide polymorphisms (SNPs), other kinds of DNA molecular defects have emerged as significant disease-causing mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 146 publications
(188 reference statements)
0
2
0
Order By: Relevance
“…Many evidences reveal the causal relationship between CNVs and many human disease phenotypes, including scores of known genomic diseases and hundreds of complex disease traits [2][3][4]. One of the essential issues in CNV research is to understand how CNVs affect the occurrence of diseases [5,6].…”
Section: Integrated Analysis Of Cnv Gene Expression and Disease Statmentioning
confidence: 99%
“…Many evidences reveal the causal relationship between CNVs and many human disease phenotypes, including scores of known genomic diseases and hundreds of complex disease traits [2][3][4]. One of the essential issues in CNV research is to understand how CNVs affect the occurrence of diseases [5,6].…”
Section: Integrated Analysis Of Cnv Gene Expression and Disease Statmentioning
confidence: 99%
“…are an important source for genetic diversity and significantly contribute to pathogenic variants. It has been demonstrated that CNVs present in the germline DNA contribute to human diseases such as, but not limited to, neurodevelopmental disorders (Wilfert et al 2017), Parkinson's disease (La Cognata et al 2016), ALzheimer's disease (Cuccaro et al 2017) and cancer susceptibility (Krepischi et al 2012).…”
Section: Introductionmentioning
confidence: 99%